Internalized stigma, emotional dysfunction and unusual experiences in young people at risk of psychosis. Issue 2 (3rd December 2013) - Pyle, Melissa; Stewart, Suzanne L.K.; French, Paul; Byrne, Rory; Patterson, Paul; Gumley, Andrew; Birchwood, Max; Morrison, Anthony P.
Abstract: Aims: To investigate the relationship between internalized stigma, depression, social anxiety and unusual experiences in young people considered to be at risk of developing psychosis. Methods: A total of 288 participants meeting criteria for an at‐risk mental state were recruited as part of a multisite randomized controlled trial of cognitive behavioural therapy for people meeting criteria for an at risk mental state (ARMS). The sample was assessed at baseline and 6 months using measures of at risk mental states, internalized stigma, depression and social anxiety. Results: The Personal Beliefs about Experiences Questionnaire was validated for use with an ARMS sample. Correlational analyses at baseline indicated significant relationships between internalized stigma and: (i) depression; (ii) social anxiety; (iii) distress associated with unusual psychological experiences; and (iv) suicidal thinking. Regression analysis indicates negative appraisals of unusual experiences contributed significantly to depression scores at 6‐month follow up when controlling for baseline depression and unusual psychological experiences. Conclusions: These findings suggest that internalized stigma may contribute to the development and maintenance of depression in young people at risk of psychosis.